Assessment of the Impacts from the Addition of Novel Assistive Technologies in Mental Health Care. (September 2016) - Garafalo, Jenna; Nathan-Roberts, Dan
This proceeding seeks to understand changes to the current model of mental health care that will occur if computer programs and smartphone applications that augment therapy become widely used in practice. Current human factors research in home healthcare, as well as the application of the SEIPS 2.0 model to the current system of mental health care are used to predict the potential risks involved in these new technologies. This proceeding explores technologies that seek to assist in normal treatment protocols as well as technologies that are intended to replace normal psychological visits. Using this model to compare assistive versus replacement technologies for mental health treatment, it was found that replacement technologies pose greater risk and should be thoroughly assessed within the system context of mental health. This paper points to areas that should be explored further to assess the safety of these applications and to fuel designs that are safe and usable by a broader population.